Hubungan Anatar pengetahuan dan Sikap Ibu Terhadap Pemilihan Metode Alat Kontrasepsi Dalam Rahim Di Puskesmas Kayamanya Tahun 2019 - Hatijar Hatijar; Irma Suryani Saleh (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
One of the rational contraceptives is intrauterine contraception. Contraceptives that have high reversibility and effectiveness are 0.6–0.8 / 100 family planning acceptors. Descriptive research with a cross-sectional approach. The sampling technique used was total sampling with a sample of 94 KB acceptors. The population in this study were all mothers who used family planning acceptors. There is a relationship between knowledge and the choice of contraceptive use with p-value = 0.000, while the relationship between attitudes and the choice of IUD contraceptive method is p = 0.001 That there is a relationship between knowledge and attitudes of mothers towards the choice of intrauterine contraceptive method